Neuropsychiatric systemic lupus erythematosus with cerebellar vasculitis and obstructive hydrocephalus requiring decompressive craniectomy. (2nd January 2021) - Naito, Nobuhito; Kawano, Hiroshi; Yamashita, Yuya; Kondo, Mayo; Haji, Shotaro; Miyamoto, Ryosuke; Toyoda, Yuko; Kanematsu, Yasuhisa; Izumi, Yuishin; Bando, Yoshimi; Nishioka, Yasuhiko
Abstract: A 36-year-old woman who had been diagnosed with systemic lupus erythematosus (SLE) was admitted to our hospital due to increasing disease SLE activity. Despite the intensification of immunosuppressive treatment, headache newly developed and worsened. Magnetic resonance imaging (MRI) revealed spreading of a high-intensity area along the sulci of the bilateral cerebellar hemispheres. She was diagnosed with neuropsychiatric SLE and methylprednisolone (mPSL) pulse therapy was started. However, consciousness disorder due to cerebellar oedema with obstructive hydrocephalus appeared and required decompressive craniectomy. The histological findings of the biopsy specimens from cerebellar vermis were compatible with features of vasculitis. She was successfully treated adding intravenous cyclophosphamide therapy.